Modeling the relationship between velocity and time to fatigue in rowing - Hill, D. W.; Alain, C.; Kennedy, M. D. (Medicine & Science in Sports & Exercise, 2003)
INTRODUCTION: Several mathematical models describe the relationship between velocity and time to fatigue. PURPOSE: The purposes of this study were to evaluate different critical velocity (V(critical)) models applied to rowing ergometry and to investigate prediction of performance time in a 2000-m race based on results from shorter trials. METHODS: Sixteen men performed seven rowing ergometer tests. Velocity and time to fatigue data from the 200-m (approximately 0.5 min) to 1200-m (approximately 3 min) trials and from the 200-m to 2000-m (approximately 6.5 min) trials were fit to a two-parameter hyperbolic model, a three-parameter hyperbolic model, and a three-parameter exponential model. RESULTS: Including data from the 2000-m trial generally resulted in higher R2 and smaller SEE. V(critical) from the three versions of the two-parameter model were 4.71 +/- 0.28 m x s(-1), 4.80 +/- 0.27 m x s(-1), and 5.04 +/- 0.24 m x s(-1) (P < 0.001). The two three-parameter models had high R2 (0.991 and 0.990, respectively) and generated parameter estimates that appeared reasonable. Time for a 2000-m race was predicted better using the two-parameter model (r > 0.974) than using the three-parameter models (r = 0.820-0.870). CONCLUSION: It is necessary to include the relatively long 2000-m predicting trial to describe accurately the velocity-time relationship in rowing. The two-parameter model may be useful in predicting time for a 2000-m race but is not otherwise appropriate for modeling when predicting trials of <1 min duration are included. Choice of model and duration of trials must be considered when using mathematical modeling to derive V(critical) and other parameters in rowing.